Pendayagunaan Sistem Informasi Akuntansi untuk Meningkatkan Transparansi Keuangan BUMDes - Juitania, Juitania; Handayani, Puspita; Fachrizal Chaery, Ahmad Ridho (Abdimisi, 2025)
This community service activity was initiated in response to the low quality of financial recording in BUMDes Suka Negara Village, which still relied on manual bookkeeping methods that were prone to errors, inefficient, and lacked transparency. The partner’s main problems included limited accounting knowledge, insufficient technological capability, and the absence of an accountable financial reporting system. This program aimed to enhance the capacity of BUMDes management through the implementation of a digital accounting system designed to support professional, efficient, and transparent financial management. The methods included needs assessment, financial reporting training, hands-on practice using accounting applications, system implementation, and continuous mentoring and monitoring. The results indicate a significant improvement in the participants’ competencies, particularly in understanding basic accounting principles, recording transactions digitally, and generating automated financial reports. The implementation of the digital accounting system also improved operational efficiency, reduced manual errors, and strengthened financial accountability within the village institution. Furthermore, continuous monitoring helped ensure system sustainability and addressed technical challenges faced by the administrators. Overall, this program produced positive impacts on BUMDes governance and established a solid foundation for developing a modern and sustainable financial management system. Keywords: Village-Owned Enterprise; accounting digitalization; financial reporting; training; community service.